Asymptotics and Mellin-Barnes integrals - Paris, R. B. (Encyclopedia of mathematics and its applications, 2001)
Asymptotics and Mellin-Barnes Integrals provides an account of the use and properties of a type of complex integral representation that arises frequently in the study of special functions typically of interest in classical analysis and mathematical physics.